MG-111 Clinical genetics education: Building foundations using e-modules for paediatric residents. (4th December 2015) - MacKenzie, Jennifer J; Acker, Amy; Suart, Theresa; Guerin, Andrea
Abstract : Objectives: Clinical Genetics is rapidly evolving so it is essential that future physicians are equipped to practice in a genetics literate world. The goal of this project is to provide non-genetics trainees with an accessible resource to enhance their genetics education and to complement traditional teaching modalities. We are undertaking a pilot study of Paediatric residents' genetics knowledge and perceptions before and after completing the e-modules. Design/methods: We have created two e-modules highlighting common situations encountered in practice, a positive newborn screen and developmental disability/autism. The e-modules lead students through gathering information, interpreting findings, and management strategies. Basic genetic concepts, indications and limitations of testing are highlighted. The modules are designed for trainees prior to exposure to Clinical Genetics, to provide a foundation to build upon with clinical experience. The modules are available through the Queen's School of Medicine technology platform. A questionnaire assessing knowledge and comfort with genetics will be administered before, immediately after, and 6 months after the modules. Focus groups will be conducted to determine residents' perception of the modules and thematically analysed through a lens of constructivist grounded theory. Results/conclusions: The e-modules have been designed and are in the process of being implemented. By sharing our preliminary experience we hope to expand genetics education opportunities for non-genetics residents.